Analyzing Race in Asian American Congregations - Alumkal, Antony William (Sociology of religion, 2008)
Several scholars reviewing studies of contemporary Asian American religion have criticized the field and have called for increased attention to the analysis of race. However, they have not extensively discussed what this analysis should look like. This article puts forward a framework for analyzing race in congregations that combines the ecology, culture, process, and resources frames from Ammerman, et al.'s Studying Congregations: A New Handbook with concepts drawn from racial formation theory. I discuss how this approach can increase the comprehensiveness and sophistication of racial analysis of Asian American congregations, and I give examples of previous empirical studies that illustrate different aspects of this approach. Finally, I suggest fruitful areas for future research on Asian American religion.